Where Malay politeness is not apparent: A study of front counter staff interactions in Malaysian public hospitals - Kuang, C.H.; Lau, S.K.; Ang, P.S.; David, M.K. (2010)
Although we know that stereotyping is not an accurate way to appreciate human beings, nevertheless, it is still used as a means to assess human behavior and consequently, misconceptions occur. One of the dominant groups living in Malaysia is the Malays who are often perceived more positively than others. Of the three dominant ethnic groups found in peninsular Malaysia, they are often described as a graceful community which places great emphasis on respect and care for the feeling of others and are imbued with refined behavior through appropriate upbringing and religious values. The Malay community tends to avoid conflicts and where possible, they would revert to peace. Often, when expected to ask for things or to speak their minds, Malays would choose to put their meanings across indirectly or in a roundabout manner (Asmah Haji Omar, 1992; Jamaliah Mohd. Ali, 2000; Asma Abdullah and Pedersen, 2003; ndAsrul Zamani, 2003) out of the need to maintain the face of the other party. The Malay community is quite cohesive in nature for many share the same religious beliefs and core values and 'bad' or 'poor' behavior is frowned upon because it reflects poor upbringing as others might interpret their poor behaviours negatively (Asrul Zamani, 003). 'Bad' or 'poor' behavior implies behaving in ways that are not acceptable by society. This paper focuses on Malay Politeness as a notion of evaluation. The paper hopes to provide a reasonable justification to explain why some of these documented characteristics of the Malay community is less frequently manifested in the interactions of front counter Malay staffs observed in six public Malaysian hospitals. Spoken data were manually recorded and then transcribed into Roman alphabets for analysis and Brown and Levinson's (1987) politeness theory was adapted into The Malaysian context of politeness. Putting emphasis only on openings and closings in front counter services, our findings reveal that the Malay staffs are unconventional when interacting with outpatients. Possible reasons accounting for this phenomenon will be discussed in the paper.